Silk fibroin carriers with sustained release capacity for treating neurological diseases - Huang, Xinqi; An, Yumei; Yuan, Shengye; Chen, Chen; Shan, Haiyan; Zhang, Mingyang (Frontiers in Pharmacology, 2023)
Neurological diseases such as traumatic brain injury, cerebral ischemia, Parkinson’s, and Alzheimer’s disease usually occur in the central and peripheral nervous system and result in nervous dysfunction, such as cognitive impairment and motor dysfunction. Long-term clinical intervention is necessary for neurological diseases where neural stem cell transplantation has made substantial progress. However, many risks remain for cell therapy, such as puncture bleeding, postoperative infection, low transplantation success rate, and tumor formation. Sustained drug delivery, which aims to maintain the desired steady-state drug concentrations in plasma or local injection sites, is considered as a feasible option to help overcome side effects and improve the therapeutic efficiency of drugs on neurological diseases. Natural polymers such as silk fibroin have excellent biocompatibility, which can be prepared for various end-use material formats, such as microsphere, gel, coating/film, scaffold/conduit, microneedle, and enables the dynamic release of loaded drugs to achieve a desired therapeutic response. Sustained-release drug delivery systems are based on the mechanism of diffusion and degradation by altering the structures of silk fibroin and drugs, factors, and cells, which can induce nerve recovery and restore the function of the nervous system in a slow and persistent manner. Based on these desirable properties of silk fibroin as a carrier with sustained-release capacity, this paper discusses the role of various forms of silk fibroin-based drug delivery materials in treating neurological diseases in recent years.